TRADITION AND IDELOGY: DISCOURSE OF THE PILGRIMAGE TO AGLONA - Juško-Štekele, Angelika (Via Latgalica, 2016)
The purpose of this article is to characterize the tradition of pilgrimages to Aglona and the collision of religious and anti-religious ideology during the Soviet period in the latter half of the 20th century. In respect to research sources (magazine and journal articles), the research uses social constructionist theory, which provides a critical view of information taken for granted, the historical and cultural conditionality of facts, and links between knowledge, social processes, and their development.The attention of the article is not strongly focused upon the pilgrimage as a cultural phenomenon, but upon the meaning assigned to it in specific historical and cultural situations during the period of Soviet ideology. Elite discursive characterizations of 19 pilgrimages were published from 1952 to 1976 in Latvian Soviet mouthpiece publications such as the newspapers „Cīņa” (‘Struggle’), „Padomju Jaunatne” (‘Soviet Youth’), the magazine „Zvaigzne” (‘Star’), etc. From these materials a body of text has been compiled that consists of 12,893 words, which were statistically analyzed with the computer program Mono Conc pro for Windows. Content analysis of the research material utilizes the method of ideological analysis of media text developed by the professor of media pedagogy Alexandr Fedorov, looking for influencing techniques adopted by mass media such as instrumentation, projection, selection, exaggeration or embellishment of facts, insult, attribution of offensive properties, evidence presentation and stylistic simplification.The understanding of ideological structure in the article was supported by the work of the American political scientist John Zaller, who updated knowledge of informative tools used in so-called elite discourse or top-down political ideology to influence public opinion.